Community structure of macrofauna in Kuap river - Nurul Ain, Mohd Din (Universiti Malaysia Sarawak, (UNIMAS), 2008)
A study of the community structure of macrofauna in Kuap River was conducted at the main and tributaries of Kuap River. The main objectives of this study were to determine the community structure of macrofauna in Kuap River and its relation to the physico-chemical factors of the water, particle size and total organic matter. The approaches taken were to measure the physico-chemical parameters of the water and to sample the sediment for macrofauna. There were 10 taxa of macrofauna found in this study which were Polychaeta, Oligochaeta, Nematoda, Copepoda, Gastropoda, Isopoda, Foraminifera, Decapoda, Amphipoda and Priapulida. Most of the physico-chemical factors showed negative correlation with the density of macrofauna taxa.